Reformasi menuju Hukum Progresif - Raharjo, Satjipo (Unisia, 2016)
As has been generally known, Indonesian legal system nowadays suffers with a lot of weaknesses. Some people are on opinion that this is as a form of degradation of the quality of law in this country. To Overcome this situation, some effort to reconstruct paradigm of legal system is absolutely needed. The aimed effort is also called as a Progressive Law. In order to optimize this effort, the enlighment of alllegal embodied components such as education, legislation, court and legal enforcement must be made. One of key factors to create Progressive Law is human resources. Therefore, reorientation on curriculum and also teaching system on legal studies is so important in this context.